220k views
1 vote
Given BX/XC=AB/AC then (BX+XC):XC=?:AC. The ? Is equal to which expression shown?

Given BX/XC=AB/AC then (BX+XC):XC=?:AC. The ? Is equal to which expression shown?-example-1
User Rob Mason
by
5.7k points

2 Answers

3 votes
My answer is AB + AC. Hope this helps
Given BX/XC=AB/AC then (BX+XC):XC=?:AC. The ? Is equal to which expression shown?-example-1
User Iraniya Naynesh
by
5.7k points
4 votes

Answer:

AB+AC

Explanation:

Given:
(BX)/(XC)=(AB)/(AC)

To determine: (BX+XC) : XC =? : AC

We need to find ? here

We have


(BX)/(XC)=(AB)/(AC)

Add 1 both sides


(BX)/(XC)+1=(AB)/(AC)+1

Taking LCM and simplify it


(BX+XC)/(XC)=(AB+AC)/(AC)

We can write fraction as ration

(BX+XC) : XC= (AB+AC) : AC

At place of "?" we get AB+AC

Thus, option 3 is correct. AB+AC

User Douglas Frari
by
6.5k points